2022
DOI: 10.1021/acsabm.2c00017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Mechanisms of Subcutaneous Preconditioning Incubation for Neural Stem Cell Embedded Hydrogels

Abstract: Stem cells are a vital component of regenerative medicine therapies, however, only a fraction of stem cells delivered to the central nervous system following injury survive the inflammatory environment. Previously, we showed that subcutaneous preconditioning of neural stem cell (NSC) embedded hydrogels for 28 days improved spinal cord injury (SCI) functional outcomes over controls. Here, we investigated the mechanism of subcutaneous preconditioning of NSC-embedded hydrogels, with and without the known neurogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Oxygenated MACF dressings were prepared as described in our previous in vivo wound healing models 16,17,25 starting from purified chitosan (ChitoClear 43010, DDA ∼80% M w = 200 kDa, Primex, Siglufjörður, Iceland) to make MAC. 16,17,[26][27][28] To make MACF, MAC was fluorinated by dropwise addition of a methanol-PFOC mixture (Sigma Aldrich) solution in a 48 hour reaction. The polymer was then dialyzed against DI water, freeze dried, and stored in airtight containers until further use.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygenated MACF dressings were prepared as described in our previous in vivo wound healing models 16,17,25 starting from purified chitosan (ChitoClear 43010, DDA ∼80% M w = 200 kDa, Primex, Siglufjörður, Iceland) to make MAC. 16,17,[26][27][28] To make MACF, MAC was fluorinated by dropwise addition of a methanol-PFOC mixture (Sigma Aldrich) solution in a 48 hour reaction. The polymer was then dialyzed against DI water, freeze dried, and stored in airtight containers until further use.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that the constructed 3D hydrogel scaffold could be used for repairing SCI by reducing inflammatory reaction, inhibiting glial scar formation and promoting axon regeneration. Hamrangsekachaee et al embedded a 3D hydrogel by subcutaneous preconditioning to improve nerve cells survive in an inflammatory environment for treatment of SCI (Figure 5B) [49]. Studying the mechanism of subcutaneous preconditioning by measuring neurogenic markers and several cytokines.…”
Section: Hydrogel Scaffoldsmentioning
confidence: 99%
“…alginateA naturally-derived polysaccharide with excellent biocompatibility and biodegradabilityLiu et al (2022) chitosan Sugar-based biomaterial derived from shellfish with high biocompatibility, biodegradability, and lack of toxicity propertiesHam et al (2020);Hamrangsekachaee et al (2022) agarose A biomaterial candidate with water solubility and adjustable mechanical properties O'Donnell et al(2021) …”
mentioning
confidence: 99%